TIPOLOGI INOVASI SEKTOR PUBLIK PADA TIGA PROGRAM INOVATIF PEMERINTAH DAERAH KOTA SURABAYA (Tinjauan Reflektif terhadap Tiga Inovasi Pelayanan Publik Pemerintah Kota Surabaya Tahun 2018) - Kristian Widya Wicaksono (Jurnal Manajemen Pelayanan Publik, 2018)
The decentralization policy in Indonesia puts the local government as the main actor to bring their community to achieve their common purpose and goal. Thus, the local government needs to be empowered so they will have a capacity to make a significant breakthrough in their decisions and actions. In line with that need, the Indonesia central government issues a law called local innovation to develop the performance of government operation and enable the acceleration of people wealth improvement. The purpose of local innovation law is also to protect local government innovation and increase in number of local government innovations. Besides the law instrument, the attention from central government by recognizing the innovative program that has been done by local government is also very important. Therefore, the Ministry of Administrative Reform provides an award for local government innovation as an incentive for local government creative efforts.This study is conducted to explore the valid concept of public sector innovation. Furthermore, this paper will provide a reflective analysis of the three innovative programs initiated by the local government in Surabaya City based on the perspective of typologies of public sector innovation. An exploratory approach is utilized in this paper to gain valid understanding about the concept of public sector innovation and its typologies in the local level.The result of this study shows that innovation and public sector innovation is a set of academic concepts which related with newness and change and it has a serious intent to improve the quality of input, product and its impact on the customer needs. Moreover, the three innovative programs of Surabaya City local government are fulfilled four criteria of the typologies of public sector innovation, which are the creation of new service, process innovation, administrative innovation, and conceptual innovation.